Opioid Prescribing Recommendations After Mohs Micrographic Surgery and Reconstruction: A Delphi Consensus. Issue 2 (February 2021) - Donigan, Jessica M.; Srivastava, Divya; Maher, Ian; Abdelmalek, Mark; Bar, Anna A.; Blalock, Travis W.; Bordeaux, Jeremy S.; Brodland, David G.; Carroll, Bryan T.; Council, MARTHA Laurin; Duffy, Keith; Fathi, Ramin; et al.
Abstract : BACKGROUND: Prescription opioids play a large role in the opioid epidemic. Even short-term prescriptions provided postoperatively can lead to dependence. OBJECTIVE: To provide opioid prescription recommendations after Mohs micrographic surgery (MMS) and reconstruction. METHODS: This was a multi-institutional Delphi consensus study consisting of a panel of members of the American College of Mohs Surgery from various practice settings. Participants were first asked to describe scenarios in which they prescribe opioids at various frequencies. These scenarios then underwent 2 Delphi ratings rounds that aimed to identify situations in which opioid prescriptions should, or should not, be routinely prescribed. Consensus was set at ≥80% agreement. Prescription recommendations were then distributed to the panelists for feedback and approval. RESULTS: Twenty-three Mohs surgeons participated in the study. There was no scenario in which consensus was met to routinely provide an opioid prescription. However, there were several scenarios in which consensus were met to not routinely prescribe an opioid. CONCLUSION: Opioids should not be routinely prescribed to every patient undergoing MMS. Prescription recommendations for opioids after MMS and reconstruction may decrease the exposure to these drugs and help combat the opioid epidemic. Abstract : Supplemental Digital Content is Available in the Text.